THE ROLE HISTORICAL FIGURES IN WESTERN AND EASTERN LITERATURE AND FOLKLORE - Kuchqorova Shoxida Baxtiyarovna (Journals Park Publishing, 2022)
Main characters are different in Western and Eastern literature. Western authors sometimes select characters like cowboys, gunfighters, frontiersmen. However, characters are taken workers, ordinary people Eastern Literature. Characters in western fiction have limited and previously mentioned roles. Typically, folklore studies cover the recent past with an evaluation of truth or social reality of events and real-life figures.
Keywords: literature, folklore, legends, historical figures, heroes, culture.